Implementation of Deep Learning Approach in Indonesian Education - Uswatun Hasanah; Ribut Prastiwi S; Ludfi Arya W; Didit Yulian K (International Journal of Educational Technology and Society, 2025)
The current Education Curriculum in Indonesia uses a deep learning approach. This is done to create deeper and more meaningful learning. With this, it is to increase student motivation so that students are more interested in participating in learning, with this creating critical thinking students. This article discusses the implementation of the deep learning approach in Education in Indonesia. Where the deep learning approach has three elements, namely meaningful learning, mindful learning and joyful learning.